Nanocomposite Thin Films Resulting from Au Nanoclusters Dispersed in Titanium Oxide Dielectric Matrixes: the Surface Plasmon Resonance Effect - Faro, Marc Torrell; Vasilevskiy, Mikhail I.; Cavaleiro, Albano; Vaz, Filipe (IntechOpen, 2011)
None